Ecology of the northern mole vole (Ellobius talpinus) in the central regions of its range: characteristics of habitats in areas of the species' occurrence - Elena Artemieva (Theriologia Ukrainica, 2022)
Burrowers are the main creators, converters, and keepers of landscapes and soils of steppe ecosystems. The northern mole vole Ellobius talpinus (Pallas, 1770) is a rather widespread species of burrowing animals, an indicator species of various types of steppes, with a pronounced environment-forming activity. Fourteen large colonies of E. talpinus were studied in the Middle Volga region during the field seasons of 2006–2021. The agrochemical indicators of the soil characterise the possibility of developing certain steppe microstations, in which specific plant associations are formed. The parameters of soil samples and their combinations show the suitability of the formation of those plant associations that will correspond to the conditions of existence, reproduction, and feeding of burrowing rodents, in this case, the northern mole vole. The agrochemical features of steppe landscapes and habitats of the northern mole vole E. talpinus in the Middle Volga region are considered as stable trends in the formation of steppe communities. The northern mole vole E. talpinus prefers soils with a neutral or slightly alkaline pH, moderate phosphorus and calcium content, high copper and manganese content, moderate zinc content, uncontaminated by heavy metals (sometimes with an excess of cadmium content in the ancient layers of the parent rock) and rather loose (from loose sand and sandy loam to light and medium loam), which is easily carried out when digging the burrow, easily digs and deepens, for arranging chambers and passages, when extracting rhizomes, tubers, and bulbs of fodder plants. In the studied region, the steppe mole vole is generally attached to steppe and steppe landscapes, forb-feather grass-fescue steppes on parent sand and sandstone, chalk rocks; it chooses burrowing sites with steppe vegetation of various options, preferring calciphilic and psammophilic associations. The mole vole, as well as other burrowing rodents, are indicators of steppe landscapes and the preservation of soil in their biotopes, which, in turn, are indicators of the preservation of steppe habitats. The type of soil, its main features, as well as landscape characteristics of the habitat are important regional diagnostic characters of E. talpinus colonies.